Pengaruh Keterlibatan Orang Tua Terhadap Prestasi Akademik Siswa Sekolah Dasar - Via Rantari; Bunga Nur Hasanah; Dea Vinni Ervia; Tarisha Azalia Ismawan (Lembag, 2024)
This study investigates the influence of parental involvement on elementary school students' academic achievement. Using a qualitative approach, this research collected data through in-depth interviews and participant observation involving 20 parents and 10 teachers from several elementary schools. The research results show that parental involvement has a significant impact on student academic achievement. The most influential forms of involvement include assistance with learning at home, effective communication with teachers, and providing motivation and emotional support to children. Data analysis shows that students whose parents are actively involved in their education tend to have better grades and show greater interest in learning. Previous research results show that parental involvement can increase students' learning motivation and academic results. In addition, this research found several problems faced by parents, including limited time and lack of confidence in helping their children. To overcome this obstacle, it is recommended that schools provide training programs for parents and strengthen communication with them through regular meetings and communication technology. Overall, this research states that the role of parents is very important in supporting the academic achievement of elementary school students and promoting stronger collaboration between schools and parents to create a supportive learning environment.